Diversification to mitigate expropriation in the tobacco industry☆ - BENEISH, M; JANSEN, I; LEWIS, M; STUART, N (Journal of Financial Economics, 2008)
While it is well established that diversifying acquisitions by large, cash-rich firms destroy shareholder wealth, we document positive abnormal returns to such acquisitions in the tobacco industry. We show that these abnormal returns are associated with proxies for lower expected expropriation costs. Specifically, we show that wealth creation increases in the degree of domestic geographic expansion afforded by the acquisition (increasing tobacco firms’ influence in more political districts) and in the liquidity of tobacco firms’ assets (converting cash to harder-to-expropriate operating assets). We also show that the threat of expropriation constrains payments to shareholders before expropriation becomes certain in 1998.